First Application of 360-Degree Camera Technology to Marine Predator Bio-Logging - Gallagher, Austin J.; Alsudairy, Nourah A.; Shea, Brendan D.; Payne, Nicholas L.; Duarte, Carlos M. (Frontiers in Marine Science, 2021)
Animal-borne video camera systems have long-been used to capture the fine-scale behaviors and unknown aspects of the biology of marine animals. However, their utility to serve as robust scientific tools in the greater bio-logging research community has not been fully realized. Here we provide, for the first time, an application of 360-degree camera technology to a marine organism, using a large tiger shark as a proof-of-concept case study. Leveraging the three-dimensional nature of the imaging technology, we derived 224 seafloor habitat assessments over the course of the nearly 1-h track, whereby the shark was able to survey ∼23,000 square meters of seafloor; over three-times greater than the capacity of non 360-degree cameras. The resulting data provided detailed information on habitat use, diving behavior, and swimming speed, as well seafloor mapping. Our results suggest that 360-degree cameras provide complimentary benefits—and in some cases superior efficiency—than unidirectional video packages, with an enhanced capacity to map seafloor.